2019
DOI: 10.2220/biomedres.40.179
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to valproic acid during middle to late-stage corticogenesis induces learning and social behavioral abnormalities with attention deficit/hyperactivity in adult mice

Abstract: Single prenatal exposure to valproic acid (VPA) in rodents is a widely used preclinical model of autism spectrum disorder (ASD). Continuous prenatal VPA exposure has been recently proposed as a new ASD model that closely captures the neuropathological features of ASD, including increases in cerebral cortex volume and the number of cortical upper layer neurons. We investigated the influence of prenatal VPA exposure on the behavior of adult offspring of pregnant dams that received intraperitoneal injections of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The results of the study showed that VPA exposed rats had social deficits indicating their low sociability in the three-chamber sociability test. This suggested the depreciation of early stage social bonding in the VPA treated rats . The improvement of autistic-like behaviors, especially the impaired sociability in VPA exposed, was observed through early NMDA receptor function suppression by Kumar et al where memantine treatment significantly increased the time spent with a novel rat .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of the study showed that VPA exposed rats had social deficits indicating their low sociability in the three-chamber sociability test. This suggested the depreciation of early stage social bonding in the VPA treated rats . The improvement of autistic-like behaviors, especially the impaired sociability in VPA exposed, was observed through early NMDA receptor function suppression by Kumar et al where memantine treatment significantly increased the time spent with a novel rat .…”
Section: Resultsmentioning
confidence: 94%
“…This suggested the depreciation of early stage social bonding in the VPA treated rats. 46 The improvement of autistic-like behaviors, especially the impaired sociability in VPA exposed, was observed through early NMDA receptor function suppression by Kumar et al where memantine treatment significantly increased the time spent with a novel rat. 35 The excessive input signals in the brain due to the elevation in the glutamatergic transmission can most possibly be the reason for abnormal brain activity and deficits in social interaction and behavior.…”
Section: Resultsmentioning
confidence: 99%
“…VPA (200 mg/kg, i.p.) was also given at gestational day 14 (when the genesis of cortical upper layer neurons takes place) to pregnant mice [77]. Male offspring, evaluated between postnatal 8 and 9 weeks, showed typical behavioral abnormalities (impaired social interaction, increased motor activity, and learning deficits) and disturbed neural activity associated with enhanced neuronal density in the prefrontal cortex, but not somatosensory area [77].…”
Section: Neurodevelopmental Risksmentioning
confidence: 99%
“…was also given at gestational day 14 (when the genesis of cortical upper layer neurons takes place) to pregnant mice [77]. Male offspring, evaluated between postnatal 8 and 9 weeks, showed typical behavioral abnormalities (impaired social interaction, increased motor activity, and learning deficits) and disturbed neural activity associated with enhanced neuronal density in the prefrontal cortex, but not somatosensory area [77]. Kawada et al [78] administered pregnant mice with VPA (500 mg/kg) at 9.5 days gestation and as expected, the male offspring (10-week-old) presented characteristic behavioral disturbances (less exploratory activity, increased anxietylike behavior, enhanced aggression).…”
Section: Neurodevelopmental Risksmentioning
confidence: 99%
“…Through this long-standing clinical use, it has been observed that pregnant mothers treated with VPA are at an increased risk of giving birth to children that are diagnosed with ASD 20 . In mice, prenatal VPA exposure also results in offspring exhibiting many ASD-like behavioural phenotypes [21][22][23][24] , including altered social behaviour [25][26][27] . Here we explored the potential of psilocybin to ameliorate altered sociability in the prenatal VPA mouse model of autism.…”
Section: Mainmentioning
confidence: 99%